Acting 101 an instructional video on basic acting exercises - Bernardino, Hannah C.; Tuaño, Micah Divah D.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Acting 101 : An Instructional Video on Basic Acting Exercises is both an academic and artistic contribution to the University, the college and the study of acting. It innovates existing workshops, classes, and books on acting by utilizing the video as the medium of instruction. It presents basic acting exercises for the voice and body, includes vital information from some of the country's premier artists, show the basic difference between stage and screen acting, and features essential acting tips for the television medium. The paper on the other hand, documents the process the producers underwent in the production of the video leaving an organized method of how an instructional video as a thesis may be produced.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Acting -- Vocational guidance -- Philippines